Target and controlled drug delivery - Vyas, S. P.; Khar, Roop K. (New Delhi CBS Publishers & Distributers, 2002)
Targeted and Controlled Drug Dehvery (Novel Carrier Systems) will certainly underwrite the future of clinical therapeutics and preventive medicine. The advances in the realm of targeted and controlled drug delivery are epitomized through various drug carriers developed from time to time for the purpose. Most of the carrier(s) are either macromolecular drug bearing complexes or conjugates or colloidal drug container(s). The book in a systematic way presents essentials of targeted drug delivery and topics covering Liposomes, Niosomes, Resealed erythrocytes, Nanoparticles, Microspheres, Double emulsion, Submicron emulsions, Chemical drug delivery systems and Magnetically modulated drug delivery. Additionally, a section is devoted to applied targeted drug delivery to tumour, brain and bone marrow. The concepts have been well conceived and presented with the help of schematics and diagrams supported with representative examples. This makes the text easy to understand and interesting. It covers almost all important topics of academic interest taught under novel drug delivery systems advanced pharmaceutics at various universities and institutes. Since it contains detailed tabulated literature reference on each subject, it would additionally be helpful to research students as resource reference and to post-graduate students as interesting reading text material. The book has more than 1500 references, more than 372 schemeaios and 103 tables (compilation of literature reference). It is a unique, concise, up-to-date resource offering students innovative, adoptive and valuable subject matter.1. Introduction to parenteral drug delivery 2. Molecular basis of targeted drug delivery 3. Bioconjugates 4. Chemical drug delivery 5. Liposomes 6. Niosomes 7. Submicron emulsions 8. Multiple emulsions 9. Nanoparticles 10. Resealed erythrocytes 11. Microspheres 12. Magnetically modulated drug delivery 13. Drug delivery to brain 14. Drug delivery to tumour 15. Drug delivery to bone marrow.
Keywords: Novel Drug Delivery System